Problems and problem attention in the construction sector – understanding the influence of human factors (Construction Economics and Building, 2014)
Problems concerning quality and productivity in the construction sector have been a recurrent issue for many years and seem to remain in spite of various initiatives for resolving them. This situation is a result of human action. From social sciences we know that psychological factors crucially influence action design. Knowledge of this influence seems however to be underestimated in the construction sector, and could represent a missing link between strategies, plans and instructions, and the actions carried out.In order to prospect for new problem solving approaches we undertook a questionnaire-based survey to investigate how individuals in the sector perceive the importance and occurrence of, and attention directed to, different proposed causes of inadequate performance. The design of the questionnaire enabled comparisons of different answers to look beyond the respondents’ overt answers.      The result suggests that (1) the whole problem solving situation, including individual, relational and contextual problem components should be addressed as ‘the problem’; (2) the workforce has the ambition and courage to do what is expected but does not always have adequate information and the ability or resources to do it; (3) mental information distortion might be responsible for affecting the way the world is understood.